2008
DOI: 10.1101/lm.990208
|View full text |Cite
|
Sign up to set email alerts
|

Faster forgetting contributes to impaired spatial memory in the PDAPP mouse: Deficit in memory retrieval associated with increased sensitivity to interference?

Abstract: Two experiments were conducted to investigate the possibility of faster forgetting by PDAPP mice (a well-established model of Alzheimer’s disease as reported by Games and colleagues in an earlier paper). Experiment 1, using mice aged 13–16 mo, confirmed the presence of a deficit in a spatial reference memory task in the water maze by hemizygous PDAPP mice relative to littermate controls. However, after overtraining to a criterion of equivalent navigational performance, a series of memory retention tests reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…The performance displayed by two, four, and six‐month‐old mice are presented on Figure A–F. Consequently, during the second series of experiments, the number of trials by session was reduced to 12 trials, to test possible greater between‐day forgetting as previously reported by other authors using other Alzheimer mouse models (Blanchard et al, ; Daumas et al, ). First, we started to train six‐month‐old mice (eight 5XFAD; 10 WT control mice).…”
Section: Resultsmentioning
confidence: 95%
“…The performance displayed by two, four, and six‐month‐old mice are presented on Figure A–F. Consequently, during the second series of experiments, the number of trials by session was reduced to 12 trials, to test possible greater between‐day forgetting as previously reported by other authors using other Alzheimer mouse models (Blanchard et al, ; Daumas et al, ). First, we started to train six‐month‐old mice (eight 5XFAD; 10 WT control mice).…”
Section: Resultsmentioning
confidence: 95%
“…For the trials were spaced to avoid the effects of hypothermia on performance. Spaced training enhances learning in healthy mice and humans (24,25) but likely increases the difficulty of the task for hAPP mice and MCI-AD patients due to forgetting between trials (26,27). Another possibility is species differences in incentive to complete the task.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown a reversal of short-term memory deficits in overtrained transgenic mice and an elimination of the spatial memory deficits with subsequent re-training (Daumas et al, 2008; Zhang et al, 2011). Additional evidence has demonstrated that overtraining or training to criteria minimizes memory deficits in older animals (Wallace et al, 1980; Beatty et al, 1985; Stewart et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Our particular RAM protocol has the added benefit of massed training trials over several days that yields a robust spatial memory. The effects of extensive training have been reported to mitigate learning and memory deficits across various paradigms (Wallace et al, 1980; Beatty et al, 1985; Stewart et al, 1989; Daumas et al, 2008; Zhang et al, 2011). Thus, we examine the degree to which overtraining on the RAM can produce a robust spatial memory capable of withstanding TBI and preserving memory function.…”
Section: Introductionmentioning
confidence: 99%